Technological dissemination in the Portuguese payments system: an empirical analysis to the region of Santarém - Pinto, S.; Ferreira, F. (International Journal of Human Capital and Information Technology Professionals, 2010)
Nowadays, few would contest that the contribution of ICT - Information and Communication Technologies - for the progress of the payments system in Portugal has been significant. The continuous irruption of new payment forms, as well as the emergence of more attractive and profitable offers, triggers countless changes. In fact, there has been an organizational restructuring of the banks, aiming at achieving higher efficiency levels, resulting from the use of ICT. In broad terms, the payments system in Portugal has been revealing high levels of modernity. However, is that adhesion to ICT similar in all the regions that are part of the Portuguese territory? The main goal of this study focuses on an empirical analysis which allows to investigate the degree of convergence, regarding the technological dissemination for banking purposes, between the region of Santarém and the national trends.